EVALUASI VISUAL TAMAN MERBABU FAMILY PARK DI KOTA MALANG - Debora Budiyono; Hendra Kurniawan; Astri Sumiati; Selly Irma Rahma Firdaus (Universitas Tribhuwana Tunggadewi, 2022)
This study aimed to produce a recommendation to the public and the government related to efforts to deal with the problem of the visual aesthetic quality of the landscape, especially in the garden landscape. The garden landscape is necessary to evaluate visual quality using assessment methods, namely Scenic Beauty Estimation (SBE). The methods produce low, medium, and high visual aesthetic quality categories where the relationship between them supports or does not support each other. The result showed dominant results are mutually supportive or appropriate on high-value playground areas and low-value soccer fields. The Welcome Area, Rest Area, and Infiltration Area have result that does not support each other with different quality values for each photo. Recommendations in this area are adjusted to the results of the assessment based on each method in the form of design concept recommendations that lead to the SBE method.